Adjuvant radiation therapy, androgen deprivation, and docetaxel for high‐risk prostate cancer postprostatectomy: Results of NRG Oncology/RTOG study 0621. Issue 13 (21st March 2017) - Hurwitz, Mark D.; Harris, Jonathan; Sartor, Oliver; Xiao, Ying; Shayegan, Bobby; Sperduto, Paul W.; Badiozamani, Kasra R.; Lawton, Colleen A. F.; Horwitz, Eric M.; Michalski, Jeff M.; Roof, Kevin; Beyer, David C.; et al.
Abstract : BACKGROUND: Phase 3 trials have demonstrated a benefit from adjuvant radiation therapy (ART) for men who have adverse factors at radical prostatectomy (RP). However, some patients have a high risk of progression despite ART. The role of systemic therapy with ART in this high‐risk group remains to be defined. METHODS: Patients who had either a post‐RP prostate‐specific antigen (PSA) nadir > 0.2 ng/mL and a Gleason score ≥7 or a PSA nadir ≤0.2 ng/mL, a Gleason score ≥8, and a pathologic tumor (pT) classification ≥ pT3 received 6 months of androgen‐deprivation therapy (ADT) plus radiotherapy and 6 cycles of docetaxel. The primary objective was to assess whether the addition of ADT and docetaxel to ART resulted in a freedom from progression (FFP) rate ≥ 70% compared with an expected rate of 50%. Multivariate logistic and Cox regression analyses were used to model associations between factors and outcomes. RESULTS: In total, 74 patients were enrolled. The median follow‐up was 4.4 years. The pathologic tumor classification was pT2 in 4% of patients, pT3 in 95%, and pT4 in 1%. The Gleason score was 7 in 18% of patients and ≥8 in 82%. Post‐RP PSA levels were ≤0.2 ng/mL in 53% of patients and >0.2 ng/mL in 47%. The 3‐year FFP rate was 73% (95% confidence interval, 61%‐83%), and the 3‐year cumulative incidence of biochemical, distant, and local failure was 26%, 7%, and 0%, respectively. In multivariate models, postprostatectomy PSA nadir was associated with 3‐year FFP, Gleason score, and PSA with biochemical failure. Grade 3 and 4 neutropenia was common; however, only 3 episodes of febrile neutropenia occurred. Late toxicities were not impacted by the addition of systemic therapy. CONCLUSIONS: Combined ADT, docetaxel, and ART for men with high‐risk prostate cancer after prostatectomy exceeded the prespecified study endpoint of 70% 3‐year FFP. Phase 3 trials assessing combined local and systemic therapies for these high‐risk patients are warranted. Cancer 2017;123:2489–96. © 2017 American Cancer Society . Abstract : The addition of docetaxel and androgen‐deprivation therapy to adjuvant radiation therapy for men at high‐risk of failure, despite receipt of both surgery and radiation therapy, results in a significant improvement in 3‐year freedom from progression compared with historic controls who receive radiation alone. The individual contribution of hormone therapy and docetaxel in this setting will require additional appropriately designed, prospective, randomized studies.